2002
DOI: 10.1111/j.1749-6632.2002.tb04071.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Neuronal Nitric Oxide Synthase and Neuronal Sensitivity in the Brain After Brain Injury

Abstract: Injury to the central nervous system is the leading cause of disability in the United States. Neuronal death is one of the causes of disability. Among patients who survive this type of injury, various degrees of recovery in brain function are observed. The molecular basis of functional recovery is poorly understood. Clinical observations and research using experimental injury models have implicated several metabolites in the cascade of events that lead to neuronal degeneration. The levels of intracellular ATP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 142 publications
(188 reference statements)
1
23
0
7
Order By: Relevance
“…During inflammation, an increase in NO production may increase the oxidative status of the CNS. The neuronal isoform of nitric oxide synthase (nNOS) is highly responsive to changes in oxidative stress (Liu et al, 2002). Perinatal exposure to Al (5 mM) in the drinking water increased the number of nNOS immunoreactive neurons in the frontal cortex of rat pups (Kim, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…During inflammation, an increase in NO production may increase the oxidative status of the CNS. The neuronal isoform of nitric oxide synthase (nNOS) is highly responsive to changes in oxidative stress (Liu et al, 2002). Perinatal exposure to Al (5 mM) in the drinking water increased the number of nNOS immunoreactive neurons in the frontal cortex of rat pups (Kim, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Si el vasoespasmo se asocia a un aporte sanguíneo bajo puede generar isquemia o infarto cerebral. Cuando en la fase final del período isquémico se produce la revascularización, la hiperoxemia tisular vinculada al mismo posibilitaría la extensión de la lesión más allá del foco o focos isquémicos 22,30,31,41 . También existe daño secundario en relación con causas .…”
Section: Daño Cerebral Secundariounclassified
“…En el transcurso de estas reacciones se libera una inmensa cantidad de superóxido. Este radical reacciona con el NO y genera peroxinitrito, el cual posee una vida media de 1-2 s y difunde en un radio de 100 μ. Ello le permite penetrar en el núcleo, e incluso en otras células, fuera de la que le dio origen, destruyendo porciones de ADN, ARN y otros componentes moleculares 22,36 . En resumen, bien por acción mecánica bien por isquemia, algunas áreas cerebrales quedarán irreversiblemente dañadas minutos a horas después del traumatismo, mientras que otras se alterarán tan sólo funcionalmente.…”
Section: Figura 8 Cadena Transportadora De Electrones (A) Y Ciclo Deunclassified
See 1 more Smart Citation
“…The actions of eNOS in endothelial dysfunction lead to vascular and metabolic disorders and are also implicated in hypoxic-ischemic brain injury [4]. Studies have shown that hypoxic brain injury is characterized by changes in vascular growth and endothelial dysfunction [5][6][7][8]. Despite the widespread conirmation a signiicant role for NO in physiological and pathological vascular homeostasis, the role of NO in the pathogenesis of perinatal brain injury has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%